Rasionalitas Penggunaan Antibiotil dan Antijamur Pasien Infeksi Menular Seksual di Puskesmas Sekabupaten Banyumas - Purnamasari, Rizky; Purnomo, Dwi Kristian; Susanti, .; Setiawan, Didik (Jurnal Farmasi Indonesia, 2013)
This study aimed to find out hte rational in the use of antibiotic and antifungal of the patients with sexually transmitted infections at community health centers at banyumas district. Type of research was observational descriptive with cross sectional study and the data was taken retrospectively from medical records of patients. From all patients Â who entered the study population, 112 patiens positive vulvavaginal candidiasis, 57 patients positive cervicitis and 39 patients positive bacterial vaginosis. Average age of patients affected by STIs were 24 years, female. Based on patients complaints, symptoms, and the laboratory results, we have found that candidiasis patients were treated with nystatin, cervicitis with a combination of azithromycin and cefixime, whereas patients with bacterial vaginosis were treated with metronidazole. The use of antibiotic and antifungals as the treatment of sexually transmitted infections at community health centers at Banyumas district is based on parameters of the right medicine, right dose, proper indications, appropriate patient, and at the lowest cost to them and always available to their community are 100% rational.Keywords : rationality, antibiotic, sexually transmitted infections